(untitled) (Journal of Technology and Operations Management, 2014)
Due to uncertain of current economic situation, manufacturers must revise their ways to survive in their business. Manufacturing capability assumes that firms are more effective than their rivals at deploying resources. It is suggested that better performing firms are more likely to address multiple manufacturing capabilities simultaneously. In developing countries, manufacturing capabilities is a new concept. There is lack of awareness on the importance of upstream manufacturing capabilities such as product development and design. Through the email survey, a total of 89 companies representing various industries had responded. The hypotheses involved were tested using correlation and regression techniques. The results of the study support all the hypotheses.This paper provides an analysis on the relationship between knowledge transfer and manufacturing capabilities among local manufacturers in Malaysian Northern Region. .